Mirza Ghalib and the Mirs of Gujarat - Ghalib, Mirza Asadullah Khan, 1797-1869.; Imam, Mir Jaffar (New Delhi : Rupa & Co., 2003)
Selected letters reflecting the relationship between Mirza Ghalib and the Mirs of Gujarat, their bacground, achievements, and strengths as individuals and as rulers.
Includes bibliographical references (p. [251]-255).
English, Persian, and Urdu
Keywords: Poets, Urdu